Effects of two types of smartphone-based stress management programmes on depressive and anxiety symptoms among hospital nurses in Vietnam: a protocol for three-arm randomised controlled trial. Issue 4 (8th April 2019) - Imamura, Kotaro; Tran, Thuy Thi Thu; Nguyen, Huong Thanh; Kuribayashi, Kazuto; Sakuraya, Asuka; Nguyen, Anh Quoc; Bui, Thu Minh; Nguyen, Quynh Thuy; Nguyen, Kien Trung; Nguyen, Giang Thi Huong; Tran, Xuyen Thi Ngoc; Truong, Tien Quang; et al.
Abstract : Introduction: Due to an increasing demand for healthcare in low-income and middle-income countries in Asia, it is important to develop a strategy to manage work-related stress in healthcare settings, particularly among nurses in these countries. The purpose of this three-arm randomised controlled trial (RCT) is to examine the effects of a newly developed smartphone-based multimodule stress management programme on reducing severity of depressive and anxiety symptoms as primary outcomes at 3-month and 7-month follow-ups among hospital nurses in Vietnam. Methods and analysis: The target study population will be registered nurses working in a large general hospital (which employs approximately about 2000 nurses) in Vietnam. They will be invited to participate in this study. Participants who fulfil the eligibility criteria will be randomly allocated to the free-choice, multimodule stress management (intervention group A, n=360), the internet cognitive behavioural therapy (iCBT), that is, fixed-order stress management (intervention group B, n=360), or a treatment as usual control group (n=360). Two types (free-choice and fixed sequential order) of smartphone-based six-module stress management programmes will be developed. Participants in the intervention groups will be required to complete one of the programmes within 10 weeks after the baseline survey. The primary outcomes are depressive and anxiety symptoms, measured by using the Depression Anxiety and Stress Scales (DASS) at 3-month and 7 month follow-ups. Ethics and dissemination: The study procedures have been approved by the Research Ethics Review Board of Graduate School of Medicine/Faculty of Medicine, the University of Tokyo (no 11991) and the Ethical Review Board for Biomedical Research of Hanoi University of Public Health (no 346/2018/YTCC-HD3). If a significant effect of the intervention programmes will be found in the RCT, the programmes will be made available to all nurses in the hospital including the control group. If the positive effects are found in this RCT, the e-stress management programmes will be disseminated to all nurses in Vietnam. Trial registration number: UMIN000033139; Pre-results.